2013
DOI: 10.3109/07388551.2013.794124
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnological potential of microbial α-galactosidases

Abstract: The enzyme α-galactosidase (α-D-galactoside galactohydrolase; EC 3.2.1.22) catalyzes the hydrolysis of α-1,6-linked galactose residues in oligosaccharides and polymeric galactomannan. The α-galactosidases are of particular interest in view of their many potential biotechnological and medical applications. These enzymes have found wide use in various industries such as food and feed, sugar and paper and pulp for the removal of raffinose and stachyose. They are also important medically for blood group conversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 119 publications
0
43
1
5
Order By: Relevance
“…These results indicate that the immobilized enzyme can be recovered and reused, which can effectively reduce the operational cost of enzyme applications. The operational stability or reusability of the immobilized α‐galactosidase in this study was found to be better than few other immobilized α‐galactosidases reported earlier (Katrolia et al, ). Storage stability of an enzyme is an important parameter to assess its long‐term usage in the industry.…”
Section: Resultscontrasting
confidence: 55%
See 2 more Smart Citations
“…These results indicate that the immobilized enzyme can be recovered and reused, which can effectively reduce the operational cost of enzyme applications. The operational stability or reusability of the immobilized α‐galactosidase in this study was found to be better than few other immobilized α‐galactosidases reported earlier (Katrolia et al, ). Storage stability of an enzyme is an important parameter to assess its long‐term usage in the industry.…”
Section: Resultscontrasting
confidence: 55%
“…Removal of oligosaccharides from soy milk is, therefore, a major factor which can improve its consumer acceptability and popularity. The enzyme, α‐galactosidase catalyzes the hydrolysis of 1,6‐linked‐α‐galactose residues from raffinose, stachyose, and melibiose and hence is of great importance in the food and feed industries (Jang et al, ; Katrolia, Rajashekhara, Yan, & Jiang, ; Ye et al, ). α‐Galactosidases have applications in the food industry for removal of RFOs from various legumes and beans; in the beet‐sugar industry for removal of raffinose from beet sugar; and in the feed industry for improving the nutritional value of animal feed (Boopathy, Gupta, & Ramudu, ; Moon et al, ; Zhou et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, fugal a-galactosidases are optimally active within the acidic pH range (4.5-5.5) [2,27]. Despite its acid pH optimum (pH 5.5), RmgalB retained more than 90% of its activity within a broad pH range from 5.5 to 9.5, and even retained over 60% of the activity at pH 4.0 for 30 min.…”
Section: Discussionmentioning
confidence: 99%
“…They have many potential applications in industries [2]. a-Galactosidases are employed in the sugar industry to enhance sugar recovery by eliminating raffinose from sugar beet syrup.…”
mentioning
confidence: 99%